(untitled) (Journal of the College of Basic Education, 2022)
The information and communication technology revolution in the past few years has brought about qualitative changes in many aspects of life to a degree as it paved the way for the transition from the industrial society to the information society, and this revolution has taken its economic, social and cultural effects on contemporary society in an unprecedented manner in terms of quantity and quality, and the information network represents one of the Manifestations of the information revolution, as they play a fundamental role in shaping the main activities of the human being in various aspects of life. The problem of this research is the study of the Iraqi youth’s use of Internet TV channels (Watch Plus) and the limits of the gratifications achieved. According to the above, the research problem which we are about to answer the questions that are most important is: What is the degree of exposure of Iraqi youth to Internet TV channels (Watch Plus)? What is the size (density) of Iraqi youth exposure to Internet TV channels (Watch Plus)? This research is based on examining a number of hypotheses, the most important of which are: The first hypothesis: There are statistically significant differences between the amount of exposure to Internet TV channels (Watch Plus) and the motives for youth use of these channels. The second hypothesis: There are statistically significant differences between the volume of youth exposure to Internet TV channels (Watch Plus) and the results achieved from them. The importance of this study lies in the importance of the topic addressed by the researcher, and it is represented in the Iraqi youth’s use of Internet TV channels (Shahid Plus) and the limits of gratification achieved, and its importance is represented in the scarcity of Arab studies that dealt with the topic of Internet TV as a modern method that has not yet been studied, in addition to the increasing number of channels. Television broadcasts only on the Internet, the multiplicity of its objectives and the diversity of its target audience, as well as the spread of Internet TV channels among the youth, and their interaction with them by commenting or participating in the programs of these channels. This research relied mainly on the survey method, which is considered a structured effort to obtain data and information about the phenomenon in question. To find useful clues about it. It has specifically relied on the sample survey approach with regard to studying the minimum vocabulary of the research community for a specific period of time through studying the Iraqi youth population who watch Internet TV channels (Watch Plus) in order to identify the motives for watching them and to determine the quality of the gratifications that are achieved to them as a result of their exposure. The research community is represented by young men and women in the city of Baghdad, whose population is estimated according to data, statistics and information (Central Statistical Organization / Ministry of Planning), which amounted to approximately 4.665.300 million people according to 2020 estimates, and a proportional stratified random sample (cluster) was chosen Surveying according to data and statistics taken from the Ministry of Planning (the Central Bureau of Statistics) taken according to the standard (name of the governorate, sub-district, locality, and alley), and the sample size was 450 female males. The research reached a set of results, most notably: 1- (40.8%) of the respondents confirmed, in the first place, that they always use Internet TV channels (Watch Plus), and in the second place sometimes, at 34.4%. 2- (44.4%) of the respondent, in the first place, confirmed that because it is a luxury about me and my entertainment was the most motivated and used by the respondents on Internet TV channels (Watch Plus), and in second place to spend free time at a rate of (22.8%). 3- (23.9%) of the respondents indicated in the first place that you would help me to follow up everything that is new and exclusive most of the benefits achieved from watching Internet TV channels (Watch Plus), and in the second place to spend free time at a rate of (25.1%). 4-The respondents (31.3%) confirmed, first place, that drama is the most favorite content for them to watch on internet TV channels (Watch Plus), and competitions ranked second.